Neuromyelitis optica: Evaluation of 871 attacks and 1, 153 treatment courses. Issue 2 (26th November 2015) - Kleiter, Ingo; Gahlen, Anna; Borisow, Nadja; Fischer, Katrin; Wernecke, Klaus‐Dieter; Wegner, Brigitte; Hellwig, Kerstin; Pache, Florence; Ruprecht, Klemens; Havla, Joachim; Krumbholz, Markus; Kümpfel, Tania; et al.
Abstract : Objective: Neuromyelitis optica (NMO) attacks often are severe, are difficult to treat, and leave residual deficits. Here, we analyzed the frequency, sequence, and efficacy of therapies used for NMO attacks. Methods: A retrospective review was made of patient records to assess demographic/diagnostic data, attack characteristics, therapies, and the short‐term remission status (complete remission [CR], partial remission [PR], no remission [NR]). Inclusion criteria were NMO according to Wingerchuk's 2006 criteria or aquaporin‐4 antibody–positive NMO spectrum disorder (NMOSD). Remission status was analyzed with generalized estimating equations (GEEs), a patient‐based statistical approach. Results: A total of 871 attacks in 185 patients (142 NMO/43 NMOSD, 82% female) were analyzed. The 1, 153 treatment courses comprised high‐dose intravenous steroids (HD‐S; n = 810), plasma exchange (PE; n = 192), immunoadsorption (IA; n = 38), other (n = 80), and unknown (n = 33) therapies. The first treatment course led to CR in 19.1%, PR in 64.5%, and NR in 16.4% of attacks. Second, third, fourth, and fifth treatment courses were given in 28.2%, 7.1%, 1.4%, and 0.5% of attacks, respectively. This escalation of attack therapy significantly improved outcome ( p < 0.001, Bowker test). Remission rates were higher for isolated optic neuritis versus isolated myelitis ( p < 0.001), and for unilateral versus bilateral optic neuritis ( p = 0.020). Isolated myelitis responded better to PE/IA than to HD‐S as first treatment course ( p = 0.037). Predictors of CR in multivariate GEE analysis were age (odds ratio [OR] = 0.97, p = 0.011), presence of myelitis (OR = 0.38, p = 0.002), CR from previous attack (OR = 6.85, p < 0.001), and first‐line PE/IA versus HD‐S (OR = 4.38, p = 0.006). Interpretation: Particularly myelitis and bilateral optic neuritis have poor remission rates. Escalation of attack therapy improves outcome. PE/IA may increase recovery in isolated myelitis. Ann Neurol 2016;79:206–216